PENYULUHAN HUKUM TENTANG SOSIALISASI KESADARAN MASYARAKAT DALAM NEGARA HUKUM BERDASARKAN UUD TAHUN 1945 - Muzayanah Muzayanah; Rochmani Rochmani; Safik Faozi; Sukarman Sukarman (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2021)
Community Service Activities are the implementation of the Tri Dharma of Higher Education that must be carried out in order to provide understanding to the community, especially to Prolanis Patients at the "RAHMATIKA" Primary Clinic, which is located at Pengkol hamlet Rt 05/Rw.01, Kel. Mangunsari, Kec. Gunung Pati, Semarang City by providing legal counseling on "Socialization of Public Awareness in a State of Law Based on the 1945 Constitution". We all know that the Republic of Indonesia is a state of law, so that the administration of the state is based on the 1945 Constitution, which we know as the constitution. The 1945 Constitution stipulates the legal basis for the Republic of Indonesia as a state of law, so that the government, state administrators and the public are obliged to obey and comply with the laws that apply within the Republic of Indonesia. Everyone residing and domiciled in the territory of the Republic of Indonesia, whether citizens or residents, is obliged to uphold the law and government without exception, this is as stipulated in Article 27 of the 1945 Constitution. This community service activity has the target of Patients participating in the Prolanis Program Pratama Clinic "RAHMATIKA" which is an Indonesian citizen who needs information and education related to legal awareness for the community towards state administration based on law (rechtsstaat) and not based on mere power (maachtsstaat). Considering that not all people understand about the rule of law and the awareness of the people who live in the Republic of Indonesia are obedient and obedient to the law. The 1945 Constitution of the Republic of Indonesia regulates that every citizen has the same position in law and government and is obliged to uphold the law and government without exception. This legal counseling is important and very necessary for the residents of the "RAHMATIKA" clinic, because many of them do not understand the awareness of the people who live in a legal state regulated by the 1945 Constitution. This legal counseling aims to provide understanding to Prolanis patients, so it is hoped that with This legal counseling will provide legal understanding and awareness for both Prolanis residents and can be disseminated to their families, their neighborhoods as well as the surrounding community and the wider community, thereby fostering legal awareness to understand their rights and obligations as well as being able to obey and uphold the law and act based on regulations. and applicable law.